Power Quality Detection and Classification Using S-Transform and Rule-Based Decision Tree - Zaro, Fouad; Alqam, Salah (International Journal of Electrical and Electronic Engineering & Telecommunications, 2019)
This paper presents a method for detection of Power Quality (PQ) disturbances using Stockwell’s transform. Modeling equations are used for PQ disturbance generation using MATLAB program as per IEEE standards. Signals features are extracted from the time-frequency analysis based on Stockwell’s transform. A rule-based decision tree are used to classify various PQ disturbances. It can be seen that high efﬁciency of classiﬁcation is achieved using S-transform with rule-based decision tree. Several PQ disturbances are addressed with single and combined disturbances. Results demonstrate the accuracy and robustness of the proposed method in detection and recognition of single and combined PQ disturbances under noiseless and noisy conditions. The proposed algorithm also shows good performance in comparison with other reported studies.
Keywords: Stockwell transform; Power Quality; Rule-based decision tree